(untitled) (Iraqi Journal of Medical Sciences, 2017)
Background: Human cytomegalovirus (HCMV), a member of herpes virus family, is associated with different cancers in humans, including breast and colorectal cancers. Objectives: To shed light on the possible oncogenic mechanisms exerted by HCMV on tissues at the genetic level. Methods: HCMV was propagated in medical research council-5 (MRC-5) cell line and cytopathic effects of HCMV were checked for confirming infection. Oncogenic mechanism that exerted by HCMV was screened using high-throughput real-time qPCR microarray to investigate the mRNA expression of 983 genes in 16 gene families associated with oncogenesis in human cells. Results :Twenty differentially expressed genes. Upregulated genes (SCGB1A1, MAP2K3, ITGB3, TGFB1, PTN, MMP2, AKT1, AKT2, BCL2L10, CKS1B, SERPINB4, CASP4, TOLLIP, BCL-2, SERPINB5) were mostly of oncogenic or oncopromoting activity, involved mainly in MAPK, PI3K/Akt, inflammation, and angiogenesis pathways while downregulated genes (STAT3, BAK1, BLM, RB1, and IGF2R) were mostly tumor suppressor, proapoptotic, and DNA damage repair genes. Conclusion: The current study revealed that HCMV might have an oncogenic or oncomodulating activity on normal infected cells by different intracellular pathways. Keywords: Cytomegalovirus, oncogenic viruses, mrc-5, Waffergen, SmartChip Real-Time PCR System. DOI: 10.22578/IJMS.14.4.7